Evaluation of the adsorption and desorption properties of zeolitic imidazolate framework-7 for volatile organic compounds through thermal desorption-gas chromatography. Issue 40 (5th October 2018) - Zhao, Ya-Ting; Yu, Li-Qing; Xia, Xin; Yang, Xin-Yu; Hu, Wei; Lv, Yun-Kai
Abstract : The adsorption/desorption properties of VOCs on ZIF-7 were evaluated by TD-GC. It was found that there are hydrophobic interaction, π–π stacking effect, molecular size effect and "gate-opening" effect between VOCs and ZIF-7. Abstract : The adsorption mechanism and desorption properties of volatile organic compounds (VOCs) in a zeolitic imidazolate framework (ZIF-7) were studied by on-line thermal desorption-gas chromatography (TD-GC), and a high efficiency method for determination of harmful indoor gas levels has been developed. The loading volume, loading flow rate and desorption temperature were optimized. Additionally, ZIF-7 has been proved to be an effective adsorbent and its adsorption performance is superior to that of commercial Tenax TA and activated carbon. It has been proved that ZIF-7 is an ideal adsorbent for VOCs. It was suggested that there are hydrophobic interactions, π–π stacking effects, "gate-opening" effects and molecular size effects between adsorbates and ZIF-7. Therefore, the developed ZIF-7-based TD-GC method offered an excellent performance with a detection limit of 1.22–2.38 ng (S/N = 3), a quantification limit of 4.05–7.94 ng (S/N = 10), and a good linearity ( R 2 = 0.99), and relative standard deviation values (RSD, n = 5) were found to be in the range of 1.69–7.97%, and tube-to-tube reproducibility for three parallel tubes was 8.01%.